DAMPAK LEVERAGE, LIKUIDITAS, DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS - Sufiyati; Sofia Prima Dewi; Merry Susanti; Liana Susanto (Jurnal Akuntansi, 2021)
The purpose of this study is to obtain empirical evidence whether leverage has a negative impact on profitability, whether liquidity has a negative impact on profitability, and whether sales growth has a positive impact on profitability. The population is all manufacturing companies consistently listed on the Indonesia Stock Exchange during the 2016-2019 period. Purposive sampling was used as a sampling technique. The data is processed using EVIEWS. Research on 111 data shows that leverage has a negative impact on profitability, liquidity does not have a negative impact on profitability, and sales growth does not have a positive impact on profitability. Keywords: profitability, leverage, liquidity, sales growth